A Systematic Review of Research on Social Work Practice with Single Fathers. Issue 5 (20th October 2019) - Haworth, Simon
Abstract : This paper presents a systematic literature review that explored social work practice with single fathers. The literature search identified 7 studies, both qualitative and quantitative in nature. The small number of studies identified that met the inclusion criteria suggests that single fathers are under-researched in social work, which aligns with their relative invisibility in practice and welfare debates. The findings suggest that social workers did not genuinely or comprehensively understand the needs of single fathers and did not effectively engage with them. This paper's discussion relates these findings to Doucet's interpretations of borderwork and border crossing and relates these concepts to questions of whether social work is inclusive of single fathers or assesses their needs fairly. The discussion is located within wider discourses that propose that societal assumptions about the feminised role of caring and lone parenthood exclude fathers and place responsibility for children primarily on mothers. This paper found that current research into social work with single fathers has not effectively considered the array of social influences on their capacities to parent and thus areas for future research are suggested to promote an agenda of inclusion for single fathers and greater awareness for social work and social work practitioners.